Estimation of Carbon Dioxide Greenhouse Gas Emissions from Household Activities in Bojonegoro Regency - Zumrotin, Amelia; Setyowati, Rr Diah Nugraheni; Nurmaningsih, Dyah Ratri (Andalasian International Journal of Applied Science, Engineering and Technology, 2023)
The energy sector from household activities is one of the contributors to carbon dioxide greenhouse gas emissions. The increase in population is a factor that can increase greenhouse gas emissions. This study aims to determine the value of greenhouse gas emissions and to map greenhouse gas emission zones. This research is a quantitative descriptive. The sampling method is simple random sampling and emission zone mapping using ArcMap 10.6. The data in this study were obtained by using questionnaires and direct interviews with respondents. The emission sources analyzed in this study come from the consumption and type of motor vehicle fuel, the consumption and type of cooking fuel, and the consumption of electrical energy. The highest value of greenhouse gas emissions resulting from household activities in Bojonegoro Regency is Balen District with an emission value of 139,048 tons/year. Meanwhile, the lowest greenhouse gas emission is Sekar District with an emission value of 22.725 tons/year. The total emission from household activities in Bojonegoro Regency is 2048,355 tons/year. Emission zone mapping is mapped into 10 zones. Balen sub-district is a sub-district that has the highest CO2 emission value with an emission value of 139,048 tons/year. Sekar, Kasiman, and Kedewan sub-districts are classified as sub-districts that have low CO2 emission values with emission values of 22,725 tons/year, 32,041 tons/year, and 28,498 tons/year.